Pharmacokinetics, tissue distribution, and plasma protein binding rate of curcumol in rats using liquid chromatography tandem mass spectrometry - Yang, Zhaoxu; Sun, Qingmei; Wang, Sheng; Tang, Bingbing; Yuan, Chenxing; Wu, Yue; Dai, Jiabin; Yang, Chen; Wang, Lingkun; Zhou, Qian; Wang, Jincheng; Weng, Qinjie (Frontiers in Pharmacology, 2022)
Objective: Curcumol is one of the major active ingredients isolated from the traditional Chinese medicine Curcumae Rhizoma and is reported to exhibit various bioactivities, such as anti-tumor and anti-liver fibrosis effects. However, studies of curcumol pharmacokinetics and tissue distribution are currently lacking. This study aims to characterize the pharmacokinetics, tissue distribution, and protein binding rate of curcumol. Methods: Pharmacokinetics properties of curcumol were investigated afte doses of 10, 40, and 80 mg/kg of curcumol for rats and a single dose of 2.0 mg/kg curcumol was given to rats via intravenous administration to investigate bioavailability. Tissue distribution was investigated after a single dose of 40 mg/kg of orally administered curcumol. Plasma protein binding of curcumol was studied in vitro via the rapid equilibrium dialysis system. Bound and unbound curcumol in rat plasma were analyzed to calculate the plasma protein binding rate. A UHPLC-MS/MS method was developed and validated to determine curcumol in rat plasma and tissues and applied to study the pharmacokinetics, tissue distribution, and plasma protein binding in rats. Results: After oral administration of 10, 40, and 80 mg/kg curcumol, results indicated a rapid absorption and quick elimination of curcumol in rats. The bioavailability ranging from 9.2% to 13.1% was calculated based on the area under the curves (AUC) of oral and intravenous administration of curcumol. During tissue distribution, most organs observed a maximum concentration of curcumol within 0.5-1.0 h. A high accumulation of curcumol was found in the small intestine, colon, liver, and kidney. Moreover, high protein binding rates ranging from 85.6% to 93.4% of curcumol were observed in rat plasma. Conclusion: This study characterized the pharmacokinetics, tissue distribution, and protein binding rates of curcumol in rats for the first time, which can provide a solid foundation for research into the mechanisms of curcumol’s biological function and clinical application.